2019
DOI: 10.1111/his.13986
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profile of high‐grade appendiceal mucinous neoplasm

Abstract: Aims High‐grade appendiceal mucinous neoplasm (HAMN) was recently proposed as a disease entity histologically analogous to low‐grade appendiceal mucinous neoplasm (LAMN), but characterised by high‐grade cytological atypia. The pathogenesis and clinical features of HAMN have not been fully elucidated. Methods and results Nine cases of HAMN, eight LAMN, 10 appendiceal mucinous adenocarcinomas (MACA) and five appendiceal serrated polyps resected between 2008 and 2017 contributed by three medical centres underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…KRAS hotspot mutations are very frequent in low-grade MANs and high-grade MANs, with a reported prevalence of 81% to 100%. 11,12 GNAS hotspot mutations are also more commonly enriched in low-grade MANs [11][12][13] and are frequently seen in mucinous neoplasms across various organs. 14,15 TP53 mutations are infrequent in lowgrade MANs 11,12 but are more frequent in high-grade MANs and mucinous adenocarcinomas.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS hotspot mutations are very frequent in low-grade MANs and high-grade MANs, with a reported prevalence of 81% to 100%. 11,12 GNAS hotspot mutations are also more commonly enriched in low-grade MANs [11][12][13] and are frequently seen in mucinous neoplasms across various organs. 14,15 TP53 mutations are infrequent in lowgrade MANs 11,12 but are more frequent in high-grade MANs and mucinous adenocarcinomas.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…11,12 GNAS hotspot mutations are also more commonly enriched in low-grade MANs [11][12][13] and are frequently seen in mucinous neoplasms across various organs. 14,15 TP53 mutations are infrequent in lowgrade MANs 11,12 but are more frequent in high-grade MANs and mucinous adenocarcinomas. 11,12 Although the data on microsatellite instability and tumor mutation burden are relatively scarce, it has been reported that approximately 1% of mucinous adenocarcinomas have high microsatellite instability and/or have a high tumor mutation burden, whereas virtually no low-grade MANs have high microsatellite instability/high tumor mutation burden.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%
“…However, Singhi and colleagues (Singhi et al 2014 ) showed that GNAS is commonly mutated in both low-grade and high-grade disseminated appendiceal mucinous neoplasms, suggesting that GNAS mutation status is not related to the grade of appendiceal mucinous neoplasms. Similarly, Liao and colleagues (Liao et al 2020 ) recently showed that HAMN and LAMN share high rates of KRAS and GNAS co-mutations supporting a common histogenesis and distinguishing them from mucinous adenocarcinoma, which is characterized by KRAS mutations in the absence of GNAS alterations.…”
Section: Discussionmentioning
confidence: 87%
“…KRAS mutations (preferentially observed in exon 2) seem to have a pivotal role in the development of appendiceal mucinous neoplasms (Kabbani et al 2002 ; Borazanci et al 2017 ). KRAS is mutated in 41–100% of appendiceal mucinous adenomas (Szych et al 1999 ; Zauber et al 2011 ; Yantiss et al 2007 ; Tsai et al 2019 ; Liao et al 2020 ; Yanai et al 2020 ). Pai et al ( 2014 ) analysed a series of 132 appendiceal lesions, revealing that serrated lesions of the appendix often harbour KRAS mutations and only infrequently display BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The limited evidence available suggests they may be more likely to progress to PMP if there is extra-appendiceal mucin at the time of appendectomy (72). They are also more likely to contain TP53 mutations than LAMN (73).…”
Section: (I)mentioning
confidence: 99%